10.1016/S0271-7964(08)70187-3 (CrossRef Listing of Deleted DOIs, 2000)
OBJECTIVES: Breast cancer survivors (BCSs) receiving endocrine therapy frequently develop genitourinary syndrome of menopause, characterized by vaginal dryness, pain, and urinary symptoms. Fractional CO2 vaginal laser therapy has been proposed as a non-hormonal management option, but the optimal number of treatment sessions remains unclear. As preparation for a forthcoming randomized, blinded, sham-controlled trial, this dose-determining study evaluated how the number of fractional CO2 laser sessions influences urogenital symptoms and objective vaginal parameters to identify session-dependent dose-response patterns. METHODS: This single-center dose-determining study was conducted at Randers Regional Hospital, Denmark. Thirty BCSs on endocrine therapy with symptomatic genitourinary syndrome of menopause underwent five monthly sessions of fractional microablative CO2 vaginal laser using a standardized intravaginal probe protocol. Outcomes were evaluated at baseline and 4 weeks after the third, fourth, and fifth sessions. The primary outcome was vaginal dryness (VAS 0-10). Secondary outcomes included vaginal pain, itching, and soreness (VAS); sexual function (FSFI, SCS-W); urinary symptoms (UDI-6, ICIQ-FLUTSsex); and vaginal health (VHI). Statistical analyses involved paired within-participant comparisons across time points. RESULTS: Twenty-seven participants (90%) completed all five sessions. Vaginal dryness decreased significantly after three treatments, with a further incremental reduction by the fifth, representing the largest session-dependent change. FSFI scores increased significantly from baseline, with additional improvements across later sessions. SCS-W and ICIQ-FLUTSsex scores decreased steadily, while UDI-6 improved from baseline but remained stable across subsequent assessments. Treatments were well tolerated, with no serious adverse events. CONCLUSIONS: Fractional CO2 vaginal laser therapy demonstrated incremental, session-dependent changes in urogenital symptoms and vaginal health measures, with the greatest improvements after five sessions. The protocol was feasible and acceptable for BCSs receiving endocrine therapy. Overall, these findings provide clinically relevant dose-response insight to help guide optimization of treatment parameters ahead of future randomized, sham-controlled trials overall.